Oral health care offered to people with disabilities in the primary health care network: what do dentists say? - Alves, Vanessa; Cardoso, Andreia; Cavalcanti, Yuri; Padilha, Wilton (Journal of Public Health: From Theory to Practice (2198-1833), 2017)
Aim: To evaluate the oral health care offered to people with disabilities (PDs) from the perspective of dentists in João Pessoa, Paraíba, Brazil. Subjects and methods: This is a cross-sectional study with a sample of 70 dentists working in the primary health care network of João Pessoa, with sampling error of 10 %. Semi-structured interviews were conducted by a single interviewer after pilot test. Descriptively and analytically analyzed using the chi-square test (α < 0.05). The perception of dentists on oral health care offered to PDs was quantitatively and qualitatively analyzed by qualitative content analysis. Results: According to reports of dentists, OH care is offered to PDs in the primary health care network mainly through preventive procedures (51.4 %). Oral health treatment needs were not carried out completely during the treatment plan (81.4 %) due to a lack of patient cooperation (44.3 %) and the inadequate physical structure of primary health care units (8.6 %). Dentists consider that PDs do not receive adequate dental care (61.4 %). There was an association between academic training of dentists and dental assistance to PDs ( p <0.05). Dentists are of the opinion there is a need for changes in the health care network, professional training and family support of PDs. Conclusion: Oral health care is offered for PDs in the primary care network, but PDs needs are not fully met. The dentists highlighted professional training, a closer relationship with caregivers and family members, as well as changes in the health care network and improved accessibility of primary health care units as important factors.